TRANSFORMASI PERILAKU KONSUMEN MUSIK: DAMPAK LAYANAN OVER-THE-TOP (OTT) TERHADAP PEMBAJAKAN MUSIK - Agatha Gita Putuhena (Jurnal Media dan Komunikasi (MEKAS), 2023)
This study aims to understand the transformation of consumer behavior in the context of digital music, especially related to the impact of Over-The-Top (OTT) services on music piracy. The development of OTT technology and platforms has significantly affected the way consumers access, share, and buy music. The research focuses on trying to understand whether the increase in popularity of OTT services has reduced music piracy behavior among consumers. This research method involves surveying and analyzing consumer data, which includes questions about OTT service usage, music piracy, music preferences, and factors influencing consumer decisions in choosing to use or not to use official services. The results of this study provide deep insight into how OTT services have changed consumer behavior when it comes to music, as well as the extent to which they have been successful in reducing music piracy. In addition, the study also helps understand the factors that motivate consumers to stick with legitimate services or turn to music piracy. The results of this study are expected to provide guidance for the music industry and OTT service providers in developing more effective strategies in combating music piracy and meeting consumer needs.